VANDALISME KOLEKSI DI PERPUSTAKAAN SMA NEGERI 8 PEKANBARU - Citra Ayu Kinanti; Rosman Rosman; Rismayeti Rismayeti (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
This study aims to determine how the collection vandalism acts that occur in the library of SMA Negeri 8 Pekanbaru. The research method used is quantitative methods, with data collection techniques through observation, interviews, literature study, and documentation. The research sample was 99 books. The results showed that vandalism to cross certain pages was the most prevalent vandalism, amounting to 38.26%. Then the page folding vandalism was 26.95%. Hacking vandalism on certain pages 24.35%. Book vandalism that is not returned, vandalism marking sentences with 4.35% coloring. Vandalism wrote a book margin of 1.74%. Vandalism in the type of image cutting, page cutting, etc. was not found in vandalism, so the percentage was 0%.